(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study examines the understanding and perceptions of the Medan City community regarding the implementation of Final Income Tax Article 4 Paragraph 2, focusing on compliance factors and operational constraints. Using a qualitative approach, data were collected through in-depth interviews with 15 SMEs, accountants, and taxpayers, supplemented by focus group discussions (FGDs) and document analysis. The findings reveal significant disparities in understanding, with 75% of micro-SMEs demonstrating limited knowledge of tax rate calculations and taxable objects. Perceptions of unfairness stemmed from flat-rate policies perceived to disregard business profit margins, while administrative challenges—such as reporting complexity and inadequate socialization—hindered compliance. However, reputational incentives and digital service accessibility emerged as potential drivers of voluntary participation. The study underscores the urgency of regulatory simplification, sector-specific educational programs, and technology integration to strengthen tax policy legitimacy. These insights contribute a micro-social perspective critical for designing inclusive fiscal strategies in Indonesia’s urban contexts. Keywords: Tax compliance, Final Income Tax Article 4(2), public perception, fiscal justice, administrative barriers